Implementasi Undang-Undang Keterbukaan Informasi Publik Dan Transparansi Pelayanan Publik Di Jawa Timur - Wahyu Saputra (LP2M Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2019)
One of the objectives of the Law on Public Information Openness (UU KIP) is to encourage the creation of transparency in public information services to the public. The goal is at the same time as an effort to realize the implementation of democratic governance and good governance. The purpose of this study was to analyze the implementation of the UU KIP in promoting transparency in public services in East Java. The research method used in this study is a normative-empirical research method. The data analysis method used is descriptive-analytical. The results of the study indicate that the implementation of the KIP Law in encouraging transparency in public services has not been able to be carried out optimally, as evidenced by the still many complaints and public information disputes that entered the East Java Information Commission.